The effects of disclosure policy on risk management incentives and market entry - Daniel Hoang; Martin Ruckes (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2014)
This paper studies the effects of hedge disclosure requirements on corporate risk management and product market competition. The analysis is based on a simple model of market entry and shows that incumbent firms engage in risk management when these activities remain unobserved by outsiders. The resulting equilibrium is desirable from a social standpoint. Financial markets are well informed and entry is efficient. However, potential attempts for more transparency by additional disclosure requirements introduce a commitment device that provides firms with incentives to distort risk management activities thereby influencing entrant beliefs. In equililibrium, firms engage in significant risk-taking. This behavior limits entry and adversely affects the nature of competition in industries. Our findings thus suggest that more disclosure on risk management may change risk management in socially undesirable ways.
urn:nbn:de:swb:90-446642
Keywords: D82; G3; L1; M4; 330; Risk Management; Hedge Disclosures; Market Entry; Signal Jamming